2012
DOI: 10.1080/02705060.2012.679322
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of large wood and its relationship to pool formation and macroinvertebrate metrics in southeastern coastal plain streams, USA

Abstract: Large wood has important structural and functional roles in streams but there is little information on large wood dynamics in the southeastern coastal plains, USA. In this study, we surveyed 35 streams in the Choctawhatchee River watershed of southeastern Alabama. These streams were broadly classified into three categories based on land use: urban, forest, and mixed (agriculture plus forest). The number, volume, and functions of large wood were quantified. Pool number, pool spacing, and drainage areas of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The increase in taxa richness among both benthic macroinvertebrate and adult caddisfly faunas at forest sites suggested the importance of habitat heterogeneity in promoting biological diversity. Many studies have noted a link between macroinvertebrate taxa richness and increased in-stream coarse woody debris due to its use as a food source and shelter, area for biofilm colonization, ability to stabilize stream banks and channels, and indirect effects on habitat variability (Rios and Bailey 2006, Urban et al 2006, Schneider and Winemiller 2008, Houghton et al 2011, Stewart et al 2012, Pilotto et al 2014. In our study, site 6 had the highest amount of both woody debris and species richness, adding further support to the idea.…”
Section: Discussionsupporting
confidence: 85%
“…The increase in taxa richness among both benthic macroinvertebrate and adult caddisfly faunas at forest sites suggested the importance of habitat heterogeneity in promoting biological diversity. Many studies have noted a link between macroinvertebrate taxa richness and increased in-stream coarse woody debris due to its use as a food source and shelter, area for biofilm colonization, ability to stabilize stream banks and channels, and indirect effects on habitat variability (Rios and Bailey 2006, Urban et al 2006, Schneider and Winemiller 2008, Houghton et al 2011, Stewart et al 2012, Pilotto et al 2014. In our study, site 6 had the highest amount of both woody debris and species richness, adding further support to the idea.…”
Section: Discussionsupporting
confidence: 85%
“…Where riparian forests shade a substantial portion of the channel and limit photosynthesis, POM introduced from the floodplain forms the foundation of the aquatic ecosystem’s trophic cascade (Tank et al., 2010) and retention of POM for even a few hours can substantially increase the availability of nutrients to microbial and macroinvertebrate communities (Battin et al., 2008). Backwater and scour pools, overhead cover, and organic substrate associated with logjams provide important habitat for aquatic organisms (Herdrich et al., 2018; Richmond & Fausch, 1995; Stewart et al., 2012) and logjams in abandoned channels that have accreted to the floodplain provide habitat for terrestrial organisms (Harmon et al., 1986; Pettit et al., 2005). Logjams increase pressure gradients within the channel that enhance hyporheic exchange flows (Doughty et al., 2020; Hester & Doyle, 2008; Sawyer et al., 2011) and logjams obstruct flow and enhance overbank flow and lateral channel migration, thus enhancing channel‐floodplain connectivity (Collins et al., 2012; Jeffries et al., 2003; Wohl, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Where riparian forests shade a substantial portion of the channel and limit photosynthesis, POM introduced from the floodplain forms the foundation of the aquatic ecosystem's trophic cascade (Tank et al, 2010) and retention of POM for even a few hours can substantially increase the availability of nutrients to microbial and macroinvertebrate communities (Battin et al, 2008). Backwater and scour pools, overhead cover, and organic substrate associated with logjams provide important habitat for aquatic organisms (Herdrich et al, 2018;Richmond & Fausch, 1995;Stewart et al, 2012) and logjams in abandoned channels that have accreted to the floodplain provide habitat for terrestrial organisms (…”
mentioning
confidence: 99%
“…The NFM woody dams in the upper River Cover catchment resulted in pool formation in some study reaches and accumulation of finer sediments in others. Previous research has suggested that the diversity of channel units (Hilderbrand, Lemly, Dolloff, & Harpster, 1997; Stewart, Bhattarai, Mullen, Metcalf, & Reátegui‐Zirena, 2012) and sediment facies (Doeg, Marchant, Douglas, & Lake, 1989; Mathers, Rice, & Wood, 2017) can contribute to increases in local biodiversity. Further studies are necessary to investigate if this increased in‐stream habitat diversity has indeed led to the presence of more diverse ecosystems.…”
Section: Discussionmentioning
confidence: 99%